2023
DOI: 10.1097/cnd.0000000000000458
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Seronegative Myasthenia Gravis: A Single-Center Case Series

Yohei Harada,
Margaret Bettin,
Vern C. Juel
et al.

Abstract: Introduction: The course of double-seronegative myasthenia gravis (DSNMG) during and after pregnancy has not been well described. Objective: To assess the course of DSNMG during pregnancy and within 6 months postpartum. Methods: A retrospective cohort study of women with DSNMG seen in the Duke Myasthenia gravis (MG) Clinic after 2003. Results: Review of the Duke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We read with interest the article by Harada et al 1 about a series of 8 pregnant women with seronegative myasthenia gravis who were examined for the influence of pregnancy or puerperium on the severity of myasthenia. It was found that the number of myasthenia symptoms increased during the first and third trimester but most often after birth in 6 of 18 pregnancies.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest the article by Harada et al 1 about a series of 8 pregnant women with seronegative myasthenia gravis who were examined for the influence of pregnancy or puerperium on the severity of myasthenia. It was found that the number of myasthenia symptoms increased during the first and third trimester but most often after birth in 6 of 18 pregnancies.…”
Section: To the Editormentioning
confidence: 99%
“…A third limitation is that adult-onset congenital myasthenic syndrome was not taken into account and excluded when applying the inclusion/exclusion criteria. 1 Adult-onset congenital myasthenic syndrome particularly affects patients with autosomal dominant congenital myasthenic syndromes. 2 The family history does not necessarily have to be positive in patients with congenital myasthenic syndrome.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…MuSK-TNMG, like adult MUSK-MG, is often a severe disease with prominent bulbar affection and respiratory insufficiency [51]. TNMG has also been described in the children of mothers with purely ocular MG or double-seronegative MG (i.e., AChR-seronegative and MuSK-seronegative MG) [33,52]. Low-density lipoprotein receptor-related protein 4 (LRP4) antibodies have been seen in some double-seronegative MG patients, but their pathogenicity is not certain.…”
Section: Maternally Produced Autoantibodiesmentioning
confidence: 99%